2015
DOI: 10.1021/ac503892c
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Bio-Orthogonal Cross-Linker for Improved Protein/Protein Interaction Analysis

Abstract: The variety of protein cross-linkers developed in recent years illustrates the current requirement for efficient reagents optimized for mass spectrometry (MS) analysis. To date, the most widely used strategy relies on commercial cross-linkers that bear an isotopically labeled tag and N-hydroxysuccinimid-ester (NHS-ester) moieties. Moreover, an enrichment step using liquid chromatography is usually performed after enzymatic digestion of the cross-linked proteins. Unfortunately, this approach suffers from severa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 45 publications
0
37
0
Order By: Relevance
“…To provide detailed information on the VgrG-Tle1 interaction, the S VgrG-Tle1 H complex was subjected to cross-linking with the NNP9 cross-linker (Nury et al, 2015). NNP9 was specifically engineered to carry 2 NHS carbamate reactive groups, which are less prone to hydrolysis than widely used NHS esters, thus improving cross-linking efficiency and performance compared to the commercial ones (Nury et al, 2015). Mass spectrometry analysis of crosslinked peptides revealed that VgrG and Tle1 establish numerous contacts (Fig 1A,Dataset EV1).…”
Section: High-resolution Cross-linking Mass Spectrometry (Xl-ms) Mappmentioning
confidence: 99%
“…To provide detailed information on the VgrG-Tle1 interaction, the S VgrG-Tle1 H complex was subjected to cross-linking with the NNP9 cross-linker (Nury et al, 2015). NNP9 was specifically engineered to carry 2 NHS carbamate reactive groups, which are less prone to hydrolysis than widely used NHS esters, thus improving cross-linking efficiency and performance compared to the commercial ones (Nury et al, 2015). Mass spectrometry analysis of crosslinked peptides revealed that VgrG and Tle1 establish numerous contacts (Fig 1A,Dataset EV1).…”
Section: High-resolution Cross-linking Mass Spectrometry (Xl-ms) Mappmentioning
confidence: 99%
“…Moreover, the K D were similar to that we determined for full-length Hsc70 (Fig 4B). Thus, both Hsc70 SBDβ and SBD-lid contribute to fibrillar αSyn binding as for monomeric αSyn [37,38].…”
Section: Hsc70 Substrate Binding Domain and Sub-domains Retain αSyn Fmentioning
confidence: 99%
“…Hsc70 is composed of two domains, a Nucleotide Binding Domain (NBD), responsible for the chaperone ATPase activity, and a Substrate Binding Domain (SBD), that binds Hsc70 clients. We previously used lysine-reactive chemical cross-linkers and mass-spectrometry to map the surface areas within Hsc70 that interact with monomeric αSyn; all the identified areas were within the SBD (Fig 3A) [37,38]. To determine whether Hsc70 SBD retains the ability to bind αSyn fibrils we expressed and purified it.…”
Section: Hsc70 Substrate Binding Domain and Sub-domains Retain αSyn Fmentioning
confidence: 99%
See 1 more Smart Citation
“…The affinity enrichment technique is particularly useful for detection of low abundance cross-linked peptides. Affinity tagging groups [4], such as biotin [34,38,[40][41][42] antibodies, alkyne, phosphate [4], and azido [43], enable selective purification of cross-linked products by chromatography or binding to solid surface.…”
Section: Chemical Cross-linking Reagentsmentioning
confidence: 99%